2013
DOI: 10.1590/s0001-37652013005000034
|View full text |Cite
|
Sign up to set email alerts
|

Are sun- and shade-type anatomy required for the acclimation of Neoregelia cruenta?

Abstract: Sun and shade plants are often discriminated by a number of sun-and shade-type anatomies. Nonetheless, we propose that among tank-bromeliads, changes in rosette architecture satisfy the requirements for coping with contrasting light levels. The tank-bromeliad Neoregelia cruenta naturally colonises sub-habitats ranging from full exposure to direct sunlight, to shaded environments in sand ridge plains. We quantifi ed anatomical and morphological traits of leaves and rosettes of N. cruenta grown under sun and sha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 28 publications
4
6
0
Order By: Relevance
“…For other Bromelioideae species, such as Billbergia elegans and Neoregelia mucugensis from rocky fields (Pereira et al 2013) and Neoregelia cruenta (R. Graham) L. B. Sm. from the Atlantic Forest (Reinert et al 2013), a statistical difference in leaf size has been documented, with longer and narrower leaves in low-light conditions, similar to what we observed for shade leaves of the N. bahiana complex. Furthermore, Pereira et al (2013) observed a larger area and thickness of the lamina in shade leaves, as well as a higher stomatal density and lower scale density.…”
Section: Morphological and Anatomical Characters Understood As Adaptasupporting
confidence: 88%
See 3 more Smart Citations
“…For other Bromelioideae species, such as Billbergia elegans and Neoregelia mucugensis from rocky fields (Pereira et al 2013) and Neoregelia cruenta (R. Graham) L. B. Sm. from the Atlantic Forest (Reinert et al 2013), a statistical difference in leaf size has been documented, with longer and narrower leaves in low-light conditions, similar to what we observed for shade leaves of the N. bahiana complex. Furthermore, Pereira et al (2013) observed a larger area and thickness of the lamina in shade leaves, as well as a higher stomatal density and lower scale density.…”
Section: Morphological and Anatomical Characters Understood As Adaptasupporting
confidence: 88%
“…Furthermore, Pereira et al (2013) observed a larger area and thickness of the lamina in shade leaves, as well as a higher stomatal density and lower scale density. Reinert et al (2013) also found larger leaf area and fewer spinescent emergences on the margins of shade leaves. Differences in the plant architecture have also been observed: shade plants have a larger diameter and fewer leaves in the rosette (Reinert et al 2013).…”
Section: Morphological and Anatomical Characters Understood As Adaptamentioning
confidence: 77%
See 2 more Smart Citations
“…Various tropical plant species have demonstrated their ability to make such adaptations (Reinert et al 2013), particularly the Gesneriaceae species, which are known to inhabit various spots with direct sunlight, such as sunny clearings, river banks and creeks, moisture-dripping vertical rocks, steep slopes, and road-cuts (Wiehler 1983;Perret et al 2013). The diversity of habitat found in the Gesneriaceae family favors comparative studies between rupicolous and epiphyte plants.…”
Section: Introductionmentioning
confidence: 99%